Factores asociados a la calidad de vida del adulto mayor en el área urbana-México - Navarro Elías, María de Guadalupe (2013)
This research conducted in the city of Celaya, Guanajuato., In 2011, was intended to determine the factors associated with quality of life of elderly people in urban areas. Methodology: descriptive or observational and correlational design, with a sample of 118 older adults attending three centers for the elderly. SF36 instruments, Mini-Examination (MMSE), and family support met the validity and reliability and information gathering was for interview. Results: age dominates the population 60 to 74 years 78.8%, predominantly female, with 70.5%, 51.7% married, 57.7% primary education, 72.9% receive an income, 47% normal cognitive function , 55% higher family support, 63.6% did not suffer illness the past six months and 84.46% have no access to health services. The factors that showed statistical significance were age and cognitive function with quality of life, and no family support. In considering the qualitative thematic analysis with in-depth interviews with cognitive function and quality of life was obtained empirical categories: Learn / re-learn and teach, in my memories and my feelings and independence and autonomy. Conclusions: Assessment of quality of life, only with the SF-36, is incomplete but additionally valued cognitive function.